14C and Other Radionuclides in Impermeable Graphite Material Waste form Long Term Behavior. Issue 6 (28th January 2019) - Márquez, E; Piña, G; Fachinger, J; Leganés, J L
ABSTRACT: The radiocarbon ( 14 C) content of irradiated graphite is the most important problem for the management of Spanish irradiated graphite (Vandellós I NPP) as L&ILW, due to this material exceeding the maximum 14 C inventory for the C.A. El Cabril repository. Therefore, the encapsulation of graphite in an impermeable matrix and making an appropriate waste form are indicated as potential management options to be studied. The conversion of the graphite to a long-term stable glass matrix, called IGM (impermeable graphite matrix), uses a long-term stable inorganic binder which additionally encloses the graphite pore system. The world's first IGM samples made with irradiated graphite have been manufactured in CIEMAT facilities. The durability of the matrix is investigated in leaching experiments in deionized water and granitic bentonite water. The results show that ∼0.05% of 14 C is leached. A species of organic carbon was found as formate and oxalate (∼10 –1 mg/L). CO was detected as volatile specie in both media in the first leaching steps; for deionized water (∼3.10 1 mg/L) and in granitic bentonite water (ranging 1.10 1 –3.10 1 mg/L). These low values demonstrated the durability of the IGM glass matrix for final disposal.